Ice Breaking to Help the Children in Suwung Village in Starting the Process of Self-Establishment - Komang Elisa Ayumi Dewi; I Wayan Kasni (Warmadewa Press, 2022)
Education is a process that supports self-development and formation, making it possible to cope with all changes and problems with an open mind and creative approach without losing identity. This community provides Ice Breaking to Help the Children in Suwung Village in Starting the Process of Self-Establishment. This Community service Program activity aims to provide learning that can help the fostered children in Suwung Village, provide learning in a pleasant atmosphere to be applied to the fostered children in Suwung Village, and provide knowledge about models, media, and learning techniques—needed by the foster children in Suwung Village in the learning community in Suwung Village. The method of this community service is the program offered to partners in the icebreaking learning model. This learning model is carried out in two ways: playing together and singing as explained by Setyawan (2015) that icebreaking was carried out with two events, namely playing and singing. The result of this community service program show that the problems faced by partners are the lack of learning models that can help the fostered children in Suwung Village, partners need learning in a pleasant atmosphere to be applied to the fostered children in Suwung Village, and the lack of attention to models, media, and learning techniques needed by foster children in Suwung Village. Thus, this PKM activity is carried out to provide learning that can help the formation of the guided children in Suwung Village, provide learning in a pleasant atmosphere to be applied to the fostered children in Suwung Village, and provide knowledge about models, media, and learning techniques needed by the assisted children in Suwung Village in the learning community in Suwung Village.